2010
DOI: 10.1074/jbc.m109.042754
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-associated Histone Deacetylase 6 (HDAC6) Regulates Epidermal Growth Factor Receptor (EGFR) Endocytic Trafficking and Degradation

Abstract: Histone deacetylase 6 (HDAC6) is a microtubule-associated deacetylase with tubulin deacetylase activity, and it binds dynein motors. Recent studies revealed that microtubule acetylation affects the affinity and processivity of microtubule motors. These unique properties implicate a role for HDAC6 in intracellular organelle transport. Here, we show that HDAC6 associates with the endosomal compartments and controls epidermal growth factor receptor (EGFR) trafficking and degradation. We found that loss of HDAC6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 28 publications
9
126
0
1
Order By: Relevance
“…Gao et and controls EGFR trafficking and degradation (10). This is consistent with data from Deribe et al showing that HDAC6 negatively regulates EGFR endocytosis and degradation by controlling the acetylation status of α-tubulin and subsequently receptor trafficking along microtubules (11).…”
Section: Introductionsupporting
confidence: 85%
“…Gao et and controls EGFR trafficking and degradation (10). This is consistent with data from Deribe et al showing that HDAC6 negatively regulates EGFR endocytosis and degradation by controlling the acetylation status of α-tubulin and subsequently receptor trafficking along microtubules (11).…”
Section: Introductionsupporting
confidence: 85%
“…In vitro deacetylation assays also demonstrated that class IIa HDACs possess potent deacetylase activity (31). Recently, we along with other labs have demonstrated that class IIa HDACs, including HDAC4 and HDAC7, are able to potentiate sumoylation of a variety of proteins including PML, LXR, MEF2, and HIC1 (19,25,(32)(33)(34). In this study, we show for the first time that HDAC7 binds FLNB in a ubiquitination-dependent manner.…”
Section: Discussionsupporting
confidence: 61%
“…Class IIB includes HDAC6 and HDAC10. HDAC6 is a major cytoplasmic protein deacetylase whose substrates include a-tubulin and heat shock protein 90 (HSP90); it also plays a role in diverse cellular functions such as aggresome formation and epidermal growth factor receptor signaling, independent of deacetylase activity (87,124,141,154). Comparatively little is known about HDAC10 and its role in transcriptional regulation.…”
Section: B Histone Acetylationmentioning
confidence: 99%